2006
DOI: 10.1016/j.jalgebra.2006.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Co-Frobenius coalgebras

Abstract: We investigate left and right co-Frobenius coalgebras and give equivalent characterizations which prove statements dual to the characterizations of Frobenius algebras. We prove that a coalgebra is left and right coFrobenius if and only if C ∼ = Rat(C * C * ) as right C * -modules and also that this is equivalent to the fact that the functors Hom K (−, K) and Hom C * (−, C * ) from M C to C * M are isomorphic. This allows a definition of a left-right symmetric concept of co-Frobenius coalgebras that is perfectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…This adds to the previously known symmetric characterization of co-Frobenius coalgebras from [11], where it is shown that C is co-Frobenius if and only if C is isomorphic to its left (or, equivalently, to its right) rational dual Rat( C * C * ). Moreover, it is shown there that this is further equivalent to the functors C * -dual Hom C * (−, C * ) and K-dual Hom K (−, K) from C * M to K M being isomorphic when restricted to the category Rat( C * M) of left (equivalently, right) rational C * -modules which is the same as the category M C of right C-comodules (Rat( C * M) = M C ).…”
Section: Abstract Algebraic Integrals and Frobenius Categoriesmentioning
confidence: 62%
“…This adds to the previously known symmetric characterization of co-Frobenius coalgebras from [11], where it is shown that C is co-Frobenius if and only if C is isomorphic to its left (or, equivalently, to its right) rational dual Rat( C * C * ). Moreover, it is shown there that this is further equivalent to the functors C * -dual Hom C * (−, C * ) and K-dual Hom K (−, K) from C * M to K M being isomorphic when restricted to the category Rat( C * M) of left (equivalently, right) rational C * -modules which is the same as the category M C of right C-comodules (Rat( C * M) = M C ).…”
Section: Abstract Algebraic Integrals and Frobenius Categoriesmentioning
confidence: 62%
“…(ii)⇒(i) is easy, since any finitely generated left submodule of M * is closed (this is a well known fact; one can also see [I,Lemma 1…”
Section: Noetherian and Artinian Objectsmentioning
confidence: 85%
“…We note that this also follows directly: : if C * is semilocal, then every simple module is rational, since C * /J is finite dimensional semisimple. By [I,Lemma 1.4], if A = C * is a profinite algebra dual to the coalgebra C, every simple rational left C * -module S has a projective cover; it is obtained via the canonical morphism E(S * ) * → S. This shows that C * is semiperfect by an equivalent. A basic question would be to understand simple modules over such an algebra A = C * .…”
Section: Semiartinian Profinite Algebrasmentioning
confidence: 99%